The precautionary approach and risk management: Can they increase the probability of successes in fishery management? - Hilborn, Ray (2001)
Considerable progress has been made in the implementation of the Precautionary Approach to the protection of fish stocks, but applying the Precautionary Approach to the protection of fishing communities lags considerably. The principle of intergenerational equity, one of the main tenets of the Precautionary Approach, and the principle of sustainable utilization both imply that the Precautionary Approach should explicitly incorporate the protection of fishing communities, not only the resources they depend on. Risk assessment aims primarily at evaluating the consequences of various harvest strategies in terms of probabilistic statements about future trends in yields, biomass, and dangers to the stock, while risk management involves finding and implementing management policies, strategies, and tactics that reduce the risk to the communities exploiting them. Not all fishery management approaches deal equally well with risk, with some compounding rather than reducing risk. Portfolio management, whereby fishing enterprises have the ability to choose among a diverse portfolio of harvestable resources, would mitigate against the risk of fluctuations in the abundance, availability, or price of individual species. Although much remains to be achieved in better assessing risk, fishery management agencies should immediately implement risk management.